KESIAPSIAGAAN MASYARAKAT TERHADAP BAHAYA LAHAR DINGIN GUNUNG MERAPI - Wimbardana, Ramanditya (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract After the 2010 eruption of Mt. Merapi, ten million cubic meter of volcanic material ravaged settlements, infrastructures, and agriculture areas where it located at downstream area of 13 rivers. Lahar becomes threat for 1 million people who live on the flanks because it can flows along the rivers anytime. However, community is still standing in their hamlets and refuses housing relocation plan that suggested by the government. This research aims to explore community preparedness for lahar threat in Mt. Merapi flanks. Understanding this information will help policy makers for disaster risk reduction that community empowerment is needed to cope with it. Research method applied with 244 questioners distribution to household who live in four hamlets in Kali Putih riverside and lahar prone area. Analytical method used statistic approach with descriptive analysis. Many households have prepared some action in order to protect them from lahar despite they have lack of information how to face lahar. This study recommends capacity building forhousehold level and community level by local government and NGOs in lahar prone area of Mount Merapi.
Keywords: Keywords: preparedness, lahar, mount merapi